Beyond environmental education : the need for ecological awareness - Schleicher, Klaus [Verfasser] (My University, 1989)
"'Environmental education' is frequently both inadequate and inefficient, as too little attention is paid to the outside influences of its cultural, scientific and political context. Since ecological problems cannot be solved only by scientific measurement, administrative action and technological compensation, 'ecological education' is necessary to deal with the polluter in his ecological environment. It is inevitable that this type of education will combine natural and human dimensions, that is, that it will make people aware of interrelationships between biotopes and sociotopes, so that conflicts of goals between human and natural environmental demands become apparent and an evaluation of risks becomes possible. The discussion of these problems starts with references to these demands and to the interrelationship of environmental policy, public environmental awareness and environmental education. Against this background a preventive ecological education is postulated and compared with the existing curricula and teaching practice. From the differences didactic conclusions are drawn as to how the predispositions of the public, institutions and young people can be integrated into the establishment to the educational concept of ecological education. There is also a discussion of how the norms of such education will change with the actual interaction of the human and natural dimensions." (author's abstract) ((en)) "'Umwelterziehung' ist vielfach unzulänglich und ineffektiv, weil sie die äusseren Einflüsse ihres kulturellen, wissenschaftlichen und politischen Kontextes zu wenig beachtet. Da ökologische Probleme aber nicht bewältigt werden können, wenn sie nur naturwissenschaftlich vermessen, administrativ geregelt und technologisch kompensiert werden, muss sich eine 'ökologische Erziehung' auch mit dem Verursacher in seinem ökologischen Umfeld befassen. Zwangsläufig muss diese Erziehung natürliche und humane Dimensionen verbinden, d.h. Wechselbeziehungen zwischen Biotopen und Soziotopen bewusst machen, damit Zielkonflikte zwischen humanen und natürlichen Umweltansprüchen sichtbar und Risikoabschätzungen möglich werden. Die Diskussion dieser Problemlage beginnt mit Hinweisen auf diese Forderungen und die Verschränkung von Umweltpolitik, öffentlichem Umweltbewusstsein und Umwelterziehung. Vor diesem Hintergrund wird eine präventive ökologische Erziehung gefordert und mit der gegenwärtigen curricularen und unterrichtlichen Praxis verglichen. Aus den Divergenzen werden didaktische Folgerungen gezogen, wie das öffentliche, institutionelle und jugendliche Vorbewusstsein bei der Erstellung eines erziehungswissenschaftlichen Konzepts für eine ökologische Erziehung berücksichtigt werden kann. Weiterhin wird diskutiert, inwieweit die Normen einer solchen Erziehung sich durch das tatsächliche Wechselspiel der humanen und natürlichen Dimensionen verändern." (Autorenreferat)
Über eine Umwelterziehung hinaus. Die Notwendigkeit eines ökologischen Bewusstseins.
Keywords: L 1 Curricula & Lehrpläne; L 2.2 Didaktik; G 2.5 Nachhaltigkeit; G 2.4 Sozialer Wandel; Umweltbildung; Curriculum; Umweltpolitik; Umweltbewusstsein; Didaktik; Ökologie; Soziale Umwelt